HUMAN RIGHT TO WATER AND SANITATION - Bogdanović, Slavko; Jovović, Aleksandar (Law - Theory and Practice, 2013)
The subject matter elaborated in this paper is human right to water, from both international and national legal standpoints. The scope of the paper is limited to respected international law developments and the national legal systems of the countries of the South Eastern Europe (SEE). The paper contains a brief review of a current state of thing regarding an access to safe drinking water and providing of basic sanitary conditions in the world, core features of the UNGA Resolution 64/292 which has recognized the human right to water and sanitation, a historic review of the legal provisions in the SEE countires regarding freedom of general use of water, and finally a short indication of the relations between state sovereignty and human right to water. In a concluding part of the paper the authors point out a potencial need of the SEE countries to revisit the realization of the human right to water guarantied to their citizens in their legal systems and to broaden the guarantied realization of that human right up to its full scope and content.